Components of Quality of Products for Special Medical Purposes - Motuzka, Iuliia (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Products for special medical purposes are indispensable in the diet of the sick, wounded, and there are of the main factors of successful treatment and rehabilitation. This group of products has several advantages: high nutritional and biological value, physiological, easy delivery of nutrients in the human body, low level of complications and moderate cost. So, it is necessary to use of high-quality raw materials for their production, which must meet the requirements of this product group and the needs of consumers. The basic requirements for raw materials for the manufacture of products for special medical purposes are their safety, availability, confirmed clinical efficacy, high degree of purification, dispersion and solubility in water. The cost of raw materials in the production of this type of product is the main factor determining its cost and necessitates the development of the raw material base. It has been established that in the world practice of production of products for special medical purposes used to mainly vegetable and animal proteins (concentrates, isolates, hydrolyzates, peptides, and amino acids), omega-3, omega-6, omega-9 fatty acids of plant origin, glucose, fructose, herbal extracts and powders. In order to increase the biological value of food products, food fibers, vitamins and minerals are added. Necessary and urgent are the searching of domestic raw materials, which would meet the requirements for products of this group. It will stimulate the development of the production of domestic products for special medical purposes, taking into account the specific stages of treatment and restoration of the body of person, while ensuring the optimal ratio of “price-quality“.